The guide and the textbook and its importance for the intermediate stage (Journal of the College of Basic Education, 2023)
Summary of the research :Textbooks are considered one of the important means in the educational process, as it is the container that carries the scientific material, and it is the reference from which the learner draws his knowledge more than other sources. The final conclusion, in order to be in harmony with the abilities of the learners and build their cognitive competencies, is the guide for the teacher and the reliable reference for the learner. The same is the case with the guide, as it is the basic reference for the teacher who accompanies him and provides him with assistance in teaching. The teacher’s guide seeks to help the teacher refine the student and direct him according to what the education system wants. , which aims to make the student search for knowledge, and then carry out the process of organizing and employing it in a good way, and this guide also seeks to provide knowledge continuously, in addition to that, it exercises problem-solving skills in an organized and elaborate manner in a range of situations. And through the teacher's guide, the teacher is able to prepare the student so that this student is able to practice solving problems in an organized manner and in various situations, and also makes the student practice critical and creative thinking in everything that revolves around him, and also makes the student communicate with others ideally, and also makes him evaluate In addition, it makes the student love his knowledge and be sincere in it. The teacher's guide also provides the teacher with assessment strategies and tools, as well as guiding him on how to use the various teaching aids. The current research included two sections, the first included the concept of the evidence, its importance, the relationship between the evidence and the method, the components of the evidence, while the second section included the concept of the book, its elements, its importance, and its authoring methods.A research extracted from a thesis: (Evaluation of the teacher's guide for the Arabic language subject for the third intermediate grade from the point of view of the subject teachers and supervisors).